Antibiotic resistance and host immune system-induced metal bactericidal control are key factors for microbial persistence in the developing human preterm infant gut microbiome - Peters, Samantha L.; Morowitz, Michael J.; Hettich, Robert L. (Frontiers in Microbiology, 2022)
The human gut microbiome, which develops and stabilizes during the early stages of infant life, plays an essential role in host health through the production of metabolic resources and the stimulation and training of the immune system. To study colonization and community functional dynamics of the microbiota based on responses to host immune processes during the normal and dysbiotic establishment of the gut, genome-resolved metaproteomics was conducted on 91 fecal samples collected over the first 90 days of life from seventeen hospitalized premature infants. Microbial responses to antibiotic administration and host-imposed metal bactericidal control correlated with community assembly and resiliency of microbes in the developing preterm gut. Specifically, proteins related to antibiotic resistance and metal homeostasis mechanisms were predominant in persisting members in the infant gut environment over the first several weeks of life. Overall, this genome-resolved metaproteomics study provides a unique approach to study the temporal expansion and resilience of microbial colonization as it allows simultaneous examination of both host and microbial metabolic activities. Understanding the interplay between host and microbes may elucidate the microbiome's potential immunomodulatory roles relevant to necrotizing enterocolitis and other dysbiotic conditions in preterm infants.